2008
DOI: 10.1186/gb-2008-9-12-r171
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP genotyping highlights the role of natural selection in Plasmodium falciparumpopulation divergence

Abstract: An array-based SNP genotyping platform for Plasmodium falciparum is reported together with an analysis of SNP diversity in global population samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 35 publications
13
112
0
1
Order By: Relevance
“…The trend towards a negative correlation between levels of genetic diversity and malaria transmission contrasts with the pattern observed for P. falciparum , for which highest diversity is seen in high-transmission settings [8,15]. This contrast is surprising and may reflect differences in the demographic history and biology of these major human parasites.…”
Section: Resultsmentioning
confidence: 82%
“…The trend towards a negative correlation between levels of genetic diversity and malaria transmission contrasts with the pattern observed for P. falciparum , for which highest diversity is seen in high-transmission settings [8,15]. This contrast is surprising and may reflect differences in the demographic history and biology of these major human parasites.…”
Section: Resultsmentioning
confidence: 82%
“…We will call it here the "starving sex hypothesis". It has been accepted by many authors in order to account for the observed population structure of Plasmodium (Arnott et al, 2012;Branch et al, 2011;Chenet et al, 2012;Conway, 2007;Ferreira et al, 2007;Gupta et al, 2012;Imwong et al, 2006Imwong et al, , 2007Iwagami et al, 2009;Mobegi et al, 2012;Mu et al, 2005;Mzilahowa et al, 2007;Neafsey, 2013;Neafsey et al, 2008;Nkhoma et al, 2013;Schultz et al, 2010;Volkman et al, 2012a,b). It can be challenged, as we will further see, since many observations are at odds with it, both in P. falciparum and in Plasmodium vivax.…”
Section: Population Structure Of Plasmodium Andmentioning
confidence: 99%
“…Research has revealed that recombination rates are variable for P. falciparum strains and achieve the highest values for African strains (Mu et al, 2005). It was also observed that genes related to immunity are under stronger diversifying selection when compared to other genes as they have higher pN/pS ratio (Jeffares et al, 2007;Neafsey et al, 2008). Identification and characterization of such genes may be crucial for better understanding of the disease, its different clinical manifestations and potential resistance to vaccination (Richie and Saul, 2002).…”
Section: Introductionmentioning
confidence: 99%